2009
DOI: 10.1269/jrr.08131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Health Risks in Workers Staying and Working on the Terrains Contaminated with Depleted Uranium

Abstract: This study investigated health risks in workers residing and working in terrains contaminated by low ionizing radiation doses which originated from ammunition containing depleted uranium (DU). The studied population was composed of two test groups (T-I, T-II) who were occasionally exposed to DU, and two referent (R-I, R-II) groups not exposed at any time to DU. All of them were evaluated for the following: complete clinical examination and blood count, presence of immature forms and blasts, leukocyte alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…Recent data also demonstrate the modification of epigenetics marks after chronic exposure to DU [22] that could contribute to the transgenerational and the carcinogenic effects of DU. DU can induce tumorigenesis in osteoblast cell lines [50] but epidemiological [51] and in vivo studies are scarce [12]. Our data suggest that, upon chronic exposure, low levels of DU can affect cell adhesion and exerts its genotoxic effects, in the long term, in a way that is, at least in part, reminiscent of the mechanism of action of cadmium, which might involve the induction of DNA mutations and carcinogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…Recent data also demonstrate the modification of epigenetics marks after chronic exposure to DU [22] that could contribute to the transgenerational and the carcinogenic effects of DU. DU can induce tumorigenesis in osteoblast cell lines [50] but epidemiological [51] and in vivo studies are scarce [12]. Our data suggest that, upon chronic exposure, low levels of DU can affect cell adhesion and exerts its genotoxic effects, in the long term, in a way that is, at least in part, reminiscent of the mechanism of action of cadmium, which might involve the induction of DNA mutations and carcinogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…In a study it was found that the levels of CD4+ T lymphocytes in a radiation-exposed group were significantly lower as compared to the controls [113]. Increased health risk of the workers exposed to small but persistent doses of ionizing radiations from their profession as well as from the contaminated environment by depleted uranium has radiobiological effects [121]. Similarly, a study was conducted to analyze blood count parameters of the people who were residing and working in terrain where low levels of ionizing radiation doses were present [122].…”
Section: Discussionmentioning
confidence: 99%
“…There are also indications of hypoxanthine-guanine phosphoribosyl transferase (HPRT) mutation in some Gulf War veterans [40] as well as chromosomal aberrations in a German study group [45]. Two studies have found suggestive chromosomal aberrations in workers exposed to DU [46,47]. …”
Section: Chronic Low Dose Exposurementioning
confidence: 99%